Implant-prosthetic rehabilitation of hemimaxillectomy defects with CAD/CAM suprastructures - Mertens, Christian; Freudlsperger, Christian; Bodem, Jens; Krisam, Johannes; Hoffmann, Jürgen; Engel, Michael (Journal of cranio-maxillofacial surgery, 2016)
Patients with hemimaxillectomy defects after tumor surgery can alternatively be rehabilitated with dental obturators or microvascular flaps. When general medical or oncologic conditions do not permit microvascular surgery, dental obturators are the only solution, yet retention for edentulous patients is often poor. The aim of this study was to evaluate whether CAD/CAM suprastructures supported by implants placed in both residual alveolar ridges and contralateral zygomatic bone could enhance obturator stability and improve functional outcomes. Five edentulous patients with class IId hemimaxillectomy defects were included in the study. Implant-retained reconstructions were planned to support cross-arch CAD/CAM milled suprastructures. Patients had to rate their restorations on a 100-mm visual analogue scale before and after treatment. Additional evaluation was performed using the Oral Health Impact Profile (OHIP-EDENT) questionnaire. In the 5 patients, 7 conventional implants were placed in the remaining zygomatic bone and 16 in the remaining contralateral alveolar ridge. After 4 months of submerged healing, CAD/CAM suprastructures were fabricated that connected all respective implants with each other. All of the prosthetic restorations were removable and bar-retained. They all achieved good defect closure and showed significant improvements concerning general satisfaction (p = 0.0343), stability (p < 0.0001), ability to chew (p = 0.0077), esthetics (p = 0.0173) and foreign body sensation (p = 0.0207). According to the OHIP-EDENT questionnaire (p = 0.0036) the improvements were significant. During the observation period of 29.4 months, no mechanical or biological complications occurred. The CAD/CAM suprastructures improved retention in all treated patients without any complications.